Sistem Pengawasan Dana Otonomi Khsusus Aceh dan Dampaknya terhadap Pemberantasan Korupsi - Akbar, Khairil; Pasha Karim, Zahlul; Fadlullah, Nyak; Siddiq Armia, Muhammad (Integritas : Jurnal Antikorupsi, 2021)
DOKA is the biggest source of corruption that has driven distric heads in Aceh to prison. This fact raises the question, how has the DOKA monitoring system been carried out and what is the impact on corruption eradication? This study aims to explain the DOKA monitoring system and its impact on corruption eradication. The theory used is the theory of Check and Balances and the theory of Willingness & Oppurtunity. This research is classified into qualitative research with descriptive analysis techniques. The main findings of the study indicate that DOKA is not being taken seriously. This can be seen in the absence of a special supervision system and the normal supervision system for DOKA is not optimal. In addition, there is no special institution that oversees the implementation of DOKA. Such a supervisory system has no impact on corruption eradication. It needs serious improvement and a comprehensive evaluation of the use and distribution of DOKA for the realization of social welfare in Aceh.